Is foliar tissue drying and grinding required for reliable and reproducible extraction of total inorganic nutrients? A comparative study of three tissue preparation methods - Minocha, Rakesh; Long, Stephanie (Frontiers in Plant Science, 2022)
In response to abiotic and biotic stress or experimental treatment(s), foliar concentrations of inorganic nutrients and metabolites often change in concert to maintain a homeostatic balance within the cell’s environment thus allowing normal functions to carry on. Therefore, whenever possible, changes in cellular chemistry, metabolism, and gene expressions should be simultaneously evaluated using a common pool of tissue. This will help advance the knowledge needed to fill the gaps in our understanding of how these variables function together to maintain cellular homeostasis. Currently, foliar samples of trees for total inorganic nutrients and metabolic analyses are often collected at different times and are stored and processed in different ways before analyses. The objective of the present study was to evaluate whether a pool of wet (previously frozen) intact tissue that is used for metabolic and molecular work would also be suitable for analyses of foliar total inorganic nutrients. We compared quantities of nutrients extracted from wet-intact, dried-intact, and dried-ground tissues taken from a common pool of previously frozen foliage of black oak (Quercus velutina L.), sugar maple (Acer saccharum Marshall), red spruce (Picea rubens Sarg.), and white pine (Pinus strobus L.). With a few exceptions in the case of hardwoods where concentrations of total Ca, Mg, K, and P extracted from wet-intact tissue were significantly higher than dry tissue, data pooled across all collection times suggest that the extracted nutrient concentrations were comparable among the three tissue preparation methods and all for species. Based on the data presented here, it may be concluded that drying and grinding of foliage may not be necessary for nutrient analyses thus making it possible to use the same pool of tissue for total inorganic nutrients and metabolic and/or genomic analyses. To our knowledge, this is the first report on such a comparison.